CLINICAL MANIFESTATIONS AND THERAPEUTIC APPROACH IN UREMIC ENCEPHALOPATHY - Fernando Malachias de Andrade Bergamo; Gabriela Carrasco Buzatto; Maria Laura da Silva Geremias; Maria Clara Teixeira Oliveira Filocomo; Gabrielle Luigi Andrade Corrêa; Tarsila Albuquerque Coelho Gomes; Julia Tavares de Lira; Bianca Cruz Baquil; Lucas Gabriel de Lima Torres; Victoria Carvalho da Gama; Carolina de Andrade Suppi Wawginiak; Eduarda Veronezi Prata Caobianco; et al. (International Journal of Health Management Review, 2026)
Uremic encephalopathy (UE) is a severe neuropsychiatric complication resulting from renal failure, characterized by the accumulation of uremic toxins and metabolic imbalances that compromise blood-brain barrier integrity and neuronal homeostasis. Through a narrative literature review, this study aimed to synthesize current evidence regarding the pathophysiology, clinical manifestations, and therapeutic strategies for UE. The results indicate a heterogeneous clinical presentation, ranging from mild cognitive deficits and sleep disturbances to seizures and coma. Pathophysiology involves cytokine-mediated inflammatory processes and oxidative stress, exacerbated by gut dysbiosis. Although hemodialysis is the cornerstone of acute treatment, its efficacy in fully reversing cognitive damage is limited due to the inefficient clearance of protein-bound toxins. Kidney transplantation stands as the definitive intervention. It is concluded that UE management requires rigorous differential diagnosis and a multidisciplinary approach to optimize neurological outcomes and patient quality of life.